Fitness Trends From Around the Globe. (January 2021) - Kercher, Vanessa Marie; Kercher, Kyle; Bennion, Trevor; Yates, Brandon A.; Feito, Yuri; Alexander, Chris; Amaral, Paulo Costa; Soares, Waldyr; Li, Yong-Ming; Han, Jia; Liu, Yang; Wang, Ran; et al.
Abstract : Apply It!: From this article, the reader should be able to do the following: Identify top 20 fitness trends for Australia, Brazil, China, Europe, Mexico, Spain, and the United States Recognize individual and unique fitness trends represented within Australia, Brazil, China, Europe, Mexico, Spain, and the United States